Clinical and biochemical determinants of metabolic syndrome among Roma and non-Roma subjects in the eastern part of Slovakia - Fedacko, Ján; Pella, Daniel; Jarcuska, Peter; Siegfried, Leonard; Janicko, Martin; Veselíny, Eduard; Sabol, Frantisek; Jarcuska, Pavol; Mareková, Mária; Gecková, Andrea Madarasová; Pazinka, Peter; Jankajová, Monika; et al. (Central European journal of public health, 2014)
BACKGROUND: The metabolic syndrome (MS) is a clustering of cardiovascular risk. The high prevalence of metabolic syndrome among populations of lower socioeconomic status is a cause of concern and calls for an effective public health response. OBJECTIVES: The aim of this study was to determine the prevalence of metabolic syndrome in the Roma population compared with the non-Roma population in the eastern part of Slovakia and to determine the parameter which has the strongest association with metabolic syndrome. RESULTS: 123 Roma and 79 non-Roma patients with metabolic syndrome were evaluated. In the subgroup of Roma men, we found that waist circumference conferred the highest chance of MS (more than 12-times), followed by triglycerides (TG) (3.670-times). In the subgroup of non-Roma men, we found that waist circumference conferred the highest chance of MS (more than 16-times), followed by high-density lipoprotein (HDL) (4.348-times increased risk per one unit decrease in HDL). In the subgroup of Roma women as well as non-Roma women, we found that serum TG conferred the highest chance of MS, followed by waist circumference for Roma women. Comparing non-classical risk factors for MS we found that only age (with OR 1.977) and high-sensitivity C-reactive protein (hsCRP) (OR 1.887) were significant and independent predictors of MS in Roma men. Among Roma women apolipoprotein B100 was also found to be an independent predictor of MS, besides age and hsCRP. CONCLUSION: Our study confirmed that the prevalence of metabolic syndrome is strongly associated with hypertriglyceridemic waist, besides other risk factors, a marker of the atherogenic metabolic triad among younger Roma population, which may be the reason for the increased cardiovascular (CV) morbidity and mortality in elderly Roma compared with non-Roma. In light of these results, better prevention of CV events for Roma minority settlements in Slovakia should be provided.
Keywords: Body Mass Index; biologické markery; Adolescent; venkovské obyvatelstvo; lidé středního věku; Rural Population; C-reaktivní protein; lidé; Risk Factors; Adult; Middle Aged; Apolipoprotein B-100; dospělí; metabolický syndrom; Lipoproteins, HDL; obvod pasu; Age Distribution; věkové rozložení; Obesity; Female; Slovenská republika; Waist Circumference; odds ratio; Biomarkers; Lipids; Male; Roma; ženské pohlaví; rozložení podle pohlaví; Sex Distribution; mladý dospělý; C-Reactive Protein; lipidy; mužské pohlaví; apolipoprotein B-100; lipoproteiny HDL; Humans; Slovakia; index tělesné hmotnosti; Triglycerides; obezita; Young Adult; Metabolic Syndrome; triglyceridy; Romové; prevalence; charakteristiky bydlení; rizikové faktory; Residence Characteristics; Prevalence; Odds Ratio; mladiství